Education, Labour Markets and Inequality in Peru. - Figueroa, A (CRISE (Department of International Development, University of Oxford), 2008)
A paradox exists in Latin American countries: the expansion of education has been very significant in recent decades; however, the degree of inequality has not declined. The obvious question then arises: is education an equalising system? This paper seeks to solve this paradox. A theoretical model is constructed to establish the relationship between education and incomes in a socially heterogeneous capitalist society. The economic process is separated into two partial processes. The first is the education process in which education is transformed into human capital; the second is the market process in which human capital is transformed into incomes. The initial inequality in the distribution of economic and political assets (which implies a socially heterogeneous society) plays an essential role in those two processes. This role operates through the basic institutions of capitalism, democracy and the market system. A set of empirical predictions is then derived from the theoretical model. The model predicts that the education system is not income equalising; it also predicts that, given the initial inequalities and the workings of the education process, the market system is not income equalising either. Therefore, a reduction in inequality in years of schooling will not imply a fall in the degree of income inequality; moreover, equality in years of schooling does not imply equality in incomes among social groups. The set of empirical predictions is then tested against Peruvian data from 2003. Statistical consistency is found between predictions and the data. Thus the theoretical model explains the Peruvian case. Some public policy implications are derived from the theory. Further studies are certainly needed in order to test the general validity of the proposed theory.